Digitally controlled active noise reduction with integrated speech communication - Steeneken, H.J. M.; Verhave, J. (Archives of Acoustics, 2004)
Active noise reduction is a successful addition to passive ear-defenders for improvement of the sound attenuation at low frequencies. Design and assessment methods are discussed, focused on subjective and objective attenuation measurements, stability, and high noise level applications. Active noise reduction systems are suitable for integration with an intercom. For this purpose the intelligibility in combination with environmental noise is evaluated. Development of a system includes the acoustical design, the (digital) feedback control, and the speech input facility. In order to achieve optimal performance a specific audio design is required. An example of such a development is discussed.